Internet slammed again [hacking]. - Cherry, S.M.
The author describes how hackers broke new ground the weekend of 24-26 January 2003 with an unusual type of Internet attack. While most computer worms propagate by e-mail, Slammer spread over the Internet among servers and even corporate PCs running such programs as the premium version of the Office XP software suite. The afflicted computers all ran software containing Microsoft's database programs SQL Server 2000 or SQL Data Engine. At least a dozen Microsoft offerings do, hence Slammer's dizzying rate of propagation. infected computers used up to 60 percent of their processing abilities generating artificial traffic between each other. Slammer's attempts to find new computers to infect also spewed prodigious amounts of traffic throughout the Net. The enormous loads even overwhelmed servers not running the vulnerable software. The largest US automated teller network was affected, as was Microsoft's own site.
Keywords: Internet attack; Microsoft; Office XP; SQL Data Engine; SQL Server 2000.; Slammer; Automated teller network; Computer worms; Corporate PCs; Hacking; Infection; Servers